Stink Bugs and Leaffooted Bugs Are Important Fruit, Nut, Seed and Vegetable Pests - Russell F. Mizell, III (EDIS)
Stink bugs (Pentatomidae) and leaffooted bugs (Coreidae) are important direct pests of many seed, fruit, vegetable and nut crops. Recently they have become serious pests of cotton because of the reduction in pesticide use resulting from the eradication of the boll weevil and the implementation of genetically-modified cotton. This document is ENY-718, one of a series of Entomology and Nematology Department, Florida Cooperative Extension Services, Institute of Food and Agricultural Sciences, University of Florida. Publication Date: April 2005.